2010
DOI: 10.1021/jf1007055
|View full text |Cite
|
Sign up to set email alerts
|

Protein Conformational Modifications and Kinetics of Water−Protein Interactions in Milk Protein Concentrate Powder upon Aging: Effect on Solubility

Abstract: Protein conformational modifications and water-protein interactions are two major factors believed to induce instability of protein and eventually affect the solubility of milk protein concentrate (MPC) powder. To test these hypotheses, MPC was stored at different water activities (a(w) 0.0-0.85) and temperatures (25 and 45 degrees C) for up to 12 weeks. Samples were examined periodically to determine solubility, change in protein conformation by Fourier transform infrared (FTIR) spectroscopy and principal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 23 publications
7
61
0
Order By: Relevance
“…The insoluble material dissolves very slowly and requires much longer rehydration time for complete dissolution (Anema et al 2006;Mimouni et al 2009). Haque et al (2010) observed that proteinprotein interactions may be initiated by unfolding of protein molecules that eventually affects solubility of MPC upon aging. They also suggested a link between minor protein unfolding/refolding and gradual loss of solubility upon ageing of MPC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insoluble material dissolves very slowly and requires much longer rehydration time for complete dissolution (Anema et al 2006;Mimouni et al 2009). Haque et al (2010) observed that proteinprotein interactions may be initiated by unfolding of protein molecules that eventually affects solubility of MPC upon aging. They also suggested a link between minor protein unfolding/refolding and gradual loss of solubility upon ageing of MPC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the solubility of MPC decreases with time and temperature of storage (Anema et al 2006;Udabage et al 2012;Haque et al 2010). The insoluble material of MPC formed during storage, mainly consists of casein micelles (McKenna 2000; Anema et al 2006;Havea 2006).…”
Section: Introductionmentioning
confidence: 99%
“…4, with increasing a w, T 2 value for water population close to the protein surface decrease up to a w 0.45 (mc 8.2 %) and then increase for higher a w samples, indicating higher interaction with protein surface for lower a w samples. This study also show that with longer storage period water population close to the protein surface (short T 2 fraction) increased with time, indicating enhanced water-protein interactions (Haque et al 2010).…”
Section: Water-protein Interactionsmentioning
confidence: 92%
“…The NMR-T 2 results indicated the presence of three distinct populations of water molecules (differing in their interaction with and distance from protein surfaces) and that the proton signal intensity and T 2 values of proton fractions varied with storage condition (humidity, temperature) and ageing (Fig. 4) (Haque et al 2010). As shown in Fig.…”
Section: Water-protein Interactionsmentioning
confidence: 95%
See 1 more Smart Citation